Post Laparoscopic Pain Control Using Local Anesthesia through Laparoscopic Port Sites - Vejdan, Seyyed Amir; Khosravi, Malihe; Naseh, Ghodratoolah (Novelty in Biomedicine, 2014)
Background: Severe abdominal pain is not common after laparoscopic surgeries, but acute or chronic pain after operation is considerable in some patients. Post-operative Pain control after laparoscopic surgeries, is conventionally achieved using analgesics such as non-steroidal anti-inflammatory drugs (NSAIDs) and narcotics, but their administration has a lot of side effects. This study compares the efficacy and side effects of local anesthetic drugs versus conventional analgesics in post-operative pain control. Materials and Methods: This prospective investigation was conducted into two groups of patients (n=93). Group 1, as control group, was given conventional analgesics such as narcotics and NSAIDs. In investigational group, at the end of laparoscopic surgery, prior to port withdrawal, a local anesthetic mixture, a short acting (Lidocaine 2%) plus a long acting (Bupivacaine 0.5%) is instilled through the port lumen between the abdominal wall layers. The efficacy of both types of medications was compared to their efficacy and side effects. Results: 85% of the control group, received 5 to 20 ml Morphine for pain control while the others were controlled with trans-rectal NSAIDs. In the treatment group, the pain of 65% of the patients was controlled only by local anesthetic drugs, 30% required NSAIDs and the other 5% required narcotics administration for pain control. Conclusion: The administration of local anesthetic drugs after laparoscopic surgery is an effective method for pain control with a low complications rate and side effects of narcotics.